An intensive study of movement and population dynamics in Triakis megalopterus in the De Hoop Marine Protected Area, South Africa - Wagstaff, Samantha (Department of Biological Sciences, 2024)
Coastal dwelling sharks are particularly at risk of decline due to the predicted rapid change in their environment and high incidences of accidental bycatch. Effective protection typically includes managing the fishing mortality and providing marine protected areas (MPAs) as refugia. To this effect, estimating natural mortality rates and home range size is vital. Triakis megalopterus, a commonly caught, endemic coastal shark of South Africa provides an excellent opportunity for this assessment. Mark-recapture data of 924 T. megalopterus caught at two sites in the De Hoop MPA from 1996 to 2020, a no-take reserve, were used to estimate home range size and natural mortality rates. Displacement frequencies were modelled to estimate home range size and space use within the MPA. Natural mortality rates for both sexes were estimated using two methods, one based on length data, combined with pre-established growth models, and another using the probability of recapture. Triakis megalopterus at De Hoop MPA displays a high level of philopatry. Individuals show consistent small movements over periods up to thirteen years. Multiple recaptures of the same sharks indicate frequent and repeated use of home ranges in the order of 1.0 km of coastline. The best fit model suggests a high degree of central tendency in space use. Skewed sex ratios towards females could be due to sex-specific longevity or mortality. The population had low mean natural mortality rates of 0.099/yr [95% C.I. 0.088/yr to 0.112/yr] for males and 0.072/yr [95% C.I. 0.062/yr to 0.082/yr] for females as estimated from the length data. These rates were close to published findings in other studies, which used models fitted to environmental and life-history data. Survivorship estimates for T. megalopterus based on tag-recapture probabilities were lower than expected compared to length-derived natural mortality rates, but still suggest a low natural mortality rate. The difference is likely caused by deflated length-based mortality estimation, caused by the high number of large female capture lengths, tag loss and predation. In conclusion, the small movements, philopatric tendencies, sex-specific movements, and rates, and small home range of T. megalopterus suggests that populations are highly susceptible to fishing and individuals are unlikely to radiate far and replenish diminished locations.